1985
DOI: 10.1136/jnnp.48.9.876
|View full text |Cite
|
Sign up to set email alerts
|

Patient outcome in the year following severe head injury and relatives' psychiatric and social functioning.

Abstract: SUMMARY Fifty-seven consecutive severe male head injury patients together with a defined female relative were assessed at home 3, 6 and 12 months after injury in order to measure the psychiatric and social impact of the injury on the relative. Relatives were found to have significant and persistent psychiatric and social dysfunction and they considered themselves to have a high burden in caring for the relative throughout the year. No particular relationship was found to be the more vulnerable. The most freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
78
0
4

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(90 citation statements)
references
References 14 publications
8
78
0
4
Order By: Relevance
“…The French PariS-TBI study reported a decrease in caregiver burden from 1 to 4 years post-injury (Bayen et al, 2014;Bayen et al, 2013). Among 57 caregivers of patients with severe TBI, the perceived level of burden was high at the 3-, 6-and 12-months follow-up times, with a slight increase between 6 and 12 months (M. G. Livingston et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The French PariS-TBI study reported a decrease in caregiver burden from 1 to 4 years post-injury (Bayen et al, 2014;Bayen et al, 2013). Among 57 caregivers of patients with severe TBI, the perceived level of burden was high at the 3-, 6-and 12-months follow-up times, with a slight increase between 6 and 12 months (M. G. Livingston et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Those caring for and living with an adult who has experienced TBI report significant levels of burden and distress [4,5]. Clinically significant levels of anxiety, depression, and impaired social adjustment have been observed at six months post-injury for over one third of those caring for people with severe TBI [6].…”
Section: Introductionmentioning
confidence: 99%
“…According to Zeigler, the reasons for staying include feelings of guilt and fear of social condemnation, a sense of responsibility, or gratitude and fond memories. While research such as that by Livingston, et al (1985) often indicated heightened stress in family members having to cope with a brain-injured person, this is not always the case (Thomsen, 1974). Maitz (1990) suggested that adjustment is related to family characteristics such as cohesion, adaptability, marital adjustment, and affectional relations among family members.…”
mentioning
confidence: 99%
“…Caring for the injured person places a considerable burden on the family and can result in ongoing psychological dysfunction (Livingston, Brooks, & Bond, 1985).…”
mentioning
confidence: 99%